Digital Home Industry in The Context of Community Empowerment - Yanti Lidiati; Achmad Hufad; Jajat Sudrajat Ardiwinata; Joni Rahmat Pramudia; Andi Kholik (Universitas Negeri Semarang, 2023)
The community empowerment approach is closely related to increasing income to meet the necessities of life. This study aims to describe aspects of community empowerment in the development of a digital economy for local women's communities. This study uses a qualitative approach, with interviews, documentation, and observation techniques. The research results show that the success of the women's empowerment program is influenced by the level of women's digital literacy and is motivated by the urgency of family income problems in order to make ends meet. Home industrial products can be bought and sold online, supported by the implementation of digital marketing training programs, so that the women's community can manage their business well. The conclusion of this research states that the digital homes industry is effective for developing into an informal economic sector and needs to be supported by standardized government legality such as Micro, Small and Medium Enterprises (MSMEs). The importance of empowering local women in the digital economy as a means to increase family income is emphasized, highlighting the need for digital literacy and appropriate government regulations.